53BP1: a DSB escort - Mirman, Zachary (Genes Dev, 2020)
53BP1 is an enigmatic DNA damage response factor that gained prominence because it determines the efficacy of PARP1 inhibitory drugs (PARPi) in BRCA1-deficient cancers. Recent studies have elevated 53BP1 from its modest status of (yet another) DNA damage factor to master regulator of double-strand break (DSB) repair pathway choice. Our review of the literature suggests an alternative view. We propose that 53BP1 has evolved to avoid mutagenic repair outcomes and does so by controlling the processing of DNA ends and the dynamics of DSBs. The consequences of 53BP1 deficiency, such as diminished PARPi efficacy in BRCA1-deficient cells and altered repair of damaged telomeres, can be explained from this viewpoint. We further propose that some of the fidelity functions of 53BP1 coevolved with class switch recombination (CSR) in the immune system. We speculate that, rather than being deterministic in DSB repair pathway choice, 53BP1 functions as a DSB escort that guards against illegitimate and potentially tumorigenic recombination.